COVID-19 RISK ASSESSMENT IN PUBLIC TRANSPORT USING AMBIENT SENSOR DATA AND WIRELESS COMMUNICATIONS - Senturk , Izzet Fatih; ADAR, Nurettin Gökhan; Panić, Stefan; Stefanović, Časlav; Yağanoğlu, Mete; Prilinčević, Bojan (Bulletin of Natural Sciences Research, 2020)
Covid-19 causes one of the most alarming global health and economic crises in modern times. Countries around the world establish different preventing measures to stop or control Covid-19 spread. The goal of this paper is to present methods for the evaluation of indoor air quality in public transport to assess the risk of contracting Covid-19. The first part of the paper involves investigating the relationship between Covid-19 and various factors affecting indoor air quality. The focus of this paper relies on exploring existing methods to estimate the number of occupants in public transport. It is known that increased occupancy rate increases the possibility of contamination as well as indoor carbon dioxide concentration. Wireless data collection schemes will be defined that can collect data from public transportation. Collected data are envisioned to be stored in the cloud for data analytics. We will present novel methods to analyze the collected data by considering the historical data and estimate the virus contagion risk level for each public transportation vehicle in service. The methodology is expected to be applicable for other airborne diseases as well. Real-time risk levels of public transportation vehicles will be available through a mobile application so that people can choose their mode of transportation accordingly.